Clinical efficacy and pharmacokinetics of hydrocodone/acetaminophen and tramadol for control of postoperative pain in dogs - Benitez, Marian E. (Kansas State University, 2014)
Hydrocodone and tramadol are opioid analgesics. No studies have been performed to evaluate the clinical efficacy or pharmacokinetics of hydrocodone/acetaminophen and tramadol in a heterogenous population of dogs. The efficacy of tramadol in dogs has been questioned based on previous pharmacokinetic data. The objectives of this study were to evaluate the analgesic effects of hydrocodone/acetaminophen and tramadol measured by a success/failure model and to determine the pharmacokinetic profile of each drug following the second oral drug dose administration. Fifty client-owned dogs presenting for routine tibial plateau leveling osteotomy were randomized to receive either oral hydrocodone/acetaminophen or tramadol in the postoperative period. A blinded investigator using a modified Glasgow Composite Measure Pain Scale scored each animal. Treatment failures were recorded and compared statistically for differences between the two groups. Blood sampling for pharmacokinetic analysis was initiated after the second oral dose. Mean [plus or minus] SE dose of hydrocodone/acetaminophen administered was 0.5 [plus or minus] 0.04 mg/kg and 16.6 [plus or minus] 1.41 mg/kg for hydrocodone and acetaminophen, respectively. Mean [plus or minus] SE dose of tramadol administered was 5.91[plus or minus] 0.61 mg/kg. The terminal half life, maximal serum concentration (Cmax) and time to maximal serum concentration (Tmax) for tramadol were approximately 1.56 hours, 155.6 ng/mL and 3.90 hours, respectively. Plasma concentrations of the active metabolite O-desmethyltramadol (M1) were low. For hydrocodone, the Cmax and Tmax were approximately 7.90 ng/mL and 3.47 hours, respectively. Plasma concentrations of hydromorphone were low after oral hydrocodone administration. Eighteen of 48 (37.5%) dogs required additional rescue analgesic therapy. This included 10 dogs in hydrocodone group and 8 dogs in the tramadol group (p=0.628). In a group of postoperative patients, no difference in pain scoring could be detected in hydrocodone/acetaminophen and tramadol groups. The pharmacokinetics of tramadol and metabolites were similar to previous studies. Wide variations existed in tramadol drug concentrations and the effects of tramadol are likely independent of the μ-opioid receptor. There is poor metabolism of hydrocodone to hydromorphone in dogs, however, efficacy may be achieved through hydrocodone. The analgesic efficacy of tramadol, 5-7 mg/kg PO q 8 h, and hydrocodone, 0.5 mg/kg PO q 8 h, should be assessed further prior to widespread use in canine postoperative patients.
Keywords: Hydrocodone; Tramadol; Analgesia; Pharmacokinetics; Pharmacodynamics; Veterinary Medicine (0778)